2006
DOI: 10.1007/s12055-006-0498-8
|View full text |Cite
|
Sign up to set email alerts
|

D-Transposition of great vessels with intact ventricular septum presenting at 3–8 weeks: Should all go for rapid two stage arterial switch or primary arterial switch?

Abstract: Background: Current reports favour primary arterial switch (ASO) in infants with d-transposition of great vessels (d-TGA) with intact ventricular septum (IVS) who present later than 21 days. The premise is that the regressed left ventricle (LV) will still adapt to the systemic circulation.Methods: We compared a retrospective group of 11 infants (group A) who had undergone rapid two stage ASO with those (group B) who had undergone primary ASO (n=15).Results: The age range (25 -70 days), weight (2.5 -4.0 Kg), po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Studies have demonstrated that the LV mass did not necessarily predict good clinical outcomes. 6,13,14 Earlier studies have demonstrated that the initial increase in the cell size and the myocardial mass following pulmonary artery (PA) banding is mostly accounted for by the increase in the volume of mitochondria (power house), enodoplasmic reticulum (synthetic factory) but to a smaller extent by the addition of new myofibrils. 15 The same authors have shown that the microscopic and ultrastructural changes seen in regressed ventricle are similar to the changes that are found in chronic hibernating myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that the LV mass did not necessarily predict good clinical outcomes. 6,13,14 Earlier studies have demonstrated that the initial increase in the cell size and the myocardial mass following pulmonary artery (PA) banding is mostly accounted for by the increase in the volume of mitochondria (power house), enodoplasmic reticulum (synthetic factory) but to a smaller extent by the addition of new myofibrils. 15 The same authors have shown that the microscopic and ultrastructural changes seen in regressed ventricle are similar to the changes that are found in chronic hibernating myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…14 In late presenters, the combined early mortality of the rapid 2-stage ASO is higher than that for the late primary ASO (55% vs 14%). 15…”
Section: Commentmentioning
confidence: 99%